Cross-reactions between Toxocara canis and Ascaris suum in the diagnosis of visceral larva migrans by western blotting technique - Nunes, Caris Maroni [UNESP]; Tundisi, Regina Nardini; Garcia, José Fernando [UNESP]; Heinemann, Marcos Brayan; Ogassawara, Saemi; Richtzenhain, Leonardo José (FapUNIFESP (SciELO), 1997)
Visceral larva migrans (VLM) is a clinical syndrome caused by infection of man by Toxocara spp, the common roundworm of dogs and cats. Tissue migration of larval stages causes illness specially in children. Because larvae are difficult to detect in tissues, diagnosis is mostly based on serology. After the introduction of the enzyme-linked immunosorbent assay (ELISA) using the larval excretory-secretory antigen of T. canis (TES), the diagnosis specificity was greatly improved although cross-reactivity with other helminths are still being reported. In Brazil, diagnosis is routinely made after absorption of serum samples with Ascaris suum antigens, a nematode antigenicaly related with Ascaris lumbricoides which is a common intestinal nematode of children. In order to identify T. canis antigens that cross react to A. suum antigens we analyzed TES antigen by SDS-PAGE and Western blotting techniques. When we used serum samples from patients suspected of VLM and positive result by ELISA as well as a reference serum sample numerous bands were seen (molecular weight of 210-200 kDa, 116-97 kDa, 55-50 kDa and 35-29 kDa). Among these there is at least one band with molecular weight around 55-66 kDa that seem to be responsible for the cross-reactivity between T. canis and A. suum once it disappears when previous absorption of serum samples with A. suum antigens is performed.
Keywords: Ascaris suum; Immunodiagnosis; Toxocara canis antigens; Visceral larva migrans; Western blotting; parasite antigen; animal; blood; cross reaction; female; immunology; Toxocara canis; visceral larva migrans syndrome; Animals; Antigens, Helminth; Blotting, Western; Cross Reactions; Female; Larva Migrans, Visceral